Conversation Codes in Selected Nigerian TV Health Talks - Oladipo, Abiola Mary; Amoniyan, Oluwasegun; OLEKANMA, Nkpuruoma Joy (Journal of Advanced Research in Social Sciences, 2022)
A conversation entails the exchange of thoughts, ideas, emotions and questions between two or more individuals for a purpose. Conversation in the 21st century may be physical or blended. Studies have investigated discourse in friendship, negotiations, classroom and literary texts for interpretations, but little attention has been paid to the health talk in the recent time in Nigeria despite its significance in the post-Covid era. Few available linguistic analyses concentrated on doctor-patient interaction with less attention to those who are healthy at the moment but may need precautions to remain hearty. The laxness in a linguistic study on health will continue to create a gulf between health and linguistic analysis. Linguists need to engage in health jargon for proper exposition and linguistic simplification. Therefore, this research aims to analyze conversational codes in selected Channels TV health talks in Nigeria. With the application of the conversational codes by Harvey Sacks. Qualitative analysis is employed to interpret conversational codes in the data selected for the study. Out of the different episodes on Channels TV daily, five episodes on hypertension, COVID-19, heart attack, diabetes and sickle cell disorder constitute the data. The study explores the theory of conversation analysis by Harvey Sacks. The approach investigates communication systems and how discourse is constructed toward achieving the ultimate goal of interaction among discussants with minute overlaps. The study qualitatively examines turn-taking, adjacency pair, sequence, repair, opening and closing. Insight from Sacks’ approach reveals that turn-taking is frequently used in the episodes with varying percentages (35-40%). Turns are flexible, and they could be determined by the host or the guests depending on the background exposure of the host to health matters. The use of fillers varies from speaker to speaker with percentages. Socio-cultural roles affect turn construction management. The hosts often ask more questions than the guest, depending on the information the guest supplies, which determines follow-up questions. Theoretically, this study can support the theory of conversational analysis- of conversational codes. The study can be a reference for applied linguistics research insights to account for telephone calls, political interviews, classrooms and debates.